Oil Shocks and Food Inflation in Nigeria: Cointegration and Granger Causality Test - Lawali, Lukman; Yusuf, Abdullahi; Maccido, Mustapha (MultiTech Publisher, 2025)
This study uses monthly time series data from January 2012 to January 2025 to investigate the dynamic relationship between food inflation and shocks to the oil price in Nigeria. It examines how domestic oil prices, international oil prices (per US dollar), and monetary policy rates affect food inflation using the Johansen Cointegration approach, Vector Error Correction Model (VECM), and Granger Causality tests. The application of cointegration analysis is supported by the unit root tests, which demonstrate that all variables are integrated to order one. According to empirical findings, there is a significant long-run positive relationship between domestic oil prices and food inflation, implying that increases in fuel costs drive food price volatility. In contrast, international oil prices have a small and statistically insignificant long-run effect. The monetary policy rate has an unexpectedly strong positive long-run effect on food inflation, highlighting the limited effectiveness of monetary tightening in addressing cost-push inflation. Granger causality results show a bidirectional causality between domestic oil prices and food inflation, as well as a unidirectional causality between food inflation and the monetary policy rate. According to the study, Nigeria's inflationary pressures are primarily driven by energy-related costs and structural inefficiencies, not monetary factors. As a result, it recommends targeted energy reforms, improved food supply infrastructure, and a coordinated policy response to reduce the inflationary impact of oil price shocks